2017
DOI: 10.5222/head.2017.127
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Reasons Of Nurses’ Requests For Leaving Their Institution In An Educational Research Hospital

Abstract: Giriş: Bu çalışma, hemşirelerin kurumdan ayrılmak isteme nedenlerinin belirlenmesi amacıyla tanımlayıcı olarak yapılmıştır. Yöntem: Araştırmanın örneklemini 06.05.2015-24.05.2015 tarihleri arasında Ankara ilinde yer alan Sağlık Bakanlığına bağlı bir eğitim ve araştırma hastanesinde çalışan, hastaneden ayrılmak isteyen ve araştırmaya katılmaya gönüllü 38 hemşire oluşturmuştur. Verilerin toplanmasında araştırmacılar tarafından literatür taranarak oluşturulan veri toplama formu kullanılmıştır. Veri toplama formu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The present study showed that heavy workload and overtime, which are indicators of a Negative work environment , played an important role in the decision of young nurses to leave the organization. These findings are consistent with those reported in previous studies conducted in Canada (Dasgupta 2014), India (Hayward et al 2016), Turkey (Kocaşlı et al 2017) and Iran (Valizadeh et al 2016). The increase in both patient care burden and the workload of nurses due to the extension of their roles is one of the most important problems in the world experienced in relation to their work environments (RNAO 2017).…”
Section: Discussionsupporting
confidence: 92%
“…The present study showed that heavy workload and overtime, which are indicators of a Negative work environment , played an important role in the decision of young nurses to leave the organization. These findings are consistent with those reported in previous studies conducted in Canada (Dasgupta 2014), India (Hayward et al 2016), Turkey (Kocaşlı et al 2017) and Iran (Valizadeh et al 2016). The increase in both patient care burden and the workload of nurses due to the extension of their roles is one of the most important problems in the world experienced in relation to their work environments (RNAO 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Another important element that plays a role in the shortage of nurses is the fact that newly graduated nurses handle the problems of the transition process ineffectively, causing them to quit the profession sooner than would be expected (Koçaşlı et al, 2016). It is especially important to identify the problems experienced in this process so that new nurses can successfully overcome the obstacles.…”
Section: Introductionmentioning
confidence: 99%